2017
DOI: 10.21101/cejph.a5050
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dying from cancer by socio-demographic indicators in the Slovak Republic

Abstract: SUMMARYAim: Cancer mortality distribution was investigated by detailed neoplasms groups, age, sex, marital status of deceased, and regions in the Slovak Republic, and examined how these determinants influence the odds of dying due to cancer.Methods: A retrospective analysis of cancer mortality statistics registered in the Slovak Republic during the years 1996-2014. For this time period, data was available only on the underlying subgroups of cancer deaths, place of death, age, year, sex, and marital status. Bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In the case of quantified significant difference, more positive results were found mainly in the female population. These results are consistent with many other findings [29,30,32,[34][35][36][37]69]. In the male population, more positive values were found only in the case of diseases of the musculoskeletal system and connective tissue (MSCL).…”
Section: Descriptive and Difference Analysis Output-gender Health Inesupporting
confidence: 92%
“…In the case of quantified significant difference, more positive results were found mainly in the female population. These results are consistent with many other findings [29,30,32,[34][35][36][37]69]. In the male population, more positive values were found only in the case of diseases of the musculoskeletal system and connective tissue (MSCL).…”
Section: Descriptive and Difference Analysis Output-gender Health Inesupporting
confidence: 92%
“…The hectic lifestyles of men, their poor nutrition, overweight, physical inactivity or stress lead to an increased risk of cancer and other critical diseases. Simultaneously, other studies also observed excessive mortality in men (Barnes et al, 2016;Haeberer et al, 2015;Kubak et al, 2017;Ross et al, 2012;Singh-Manoux et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Ross et al (2012) agreed that male mortality is higher than female mortality, and suggested that education may be a factor that lead to close the gender gap in mortality. Gender inequalities in mortality were evidenced not only in the case of all-cause mortality, but also in the case of specific categories of mortality such as cancer (Ellison, 2016;Fernandez et al, 2000;Kubak et al, 2017), asthma, ACOS (asthma-COPD overlap syndrome) and COPD (chronic obstructive pulmonary disease) mortality (Barnes et al, 2016). In all cases, the results were more positive for women.…”
Section: Literature Reviewmentioning
confidence: 95%